Gene expression analyses on adipose tissue of Nellore peripubertal heifers reveal genes that have an impact on reproductive physiology - Henriques, Paula Suarez (2017)
Pubertal development is an outcome of genes\' interaction producing molecular signals that rule physiological mechanisms. Understanding the genetic changes surrounding the peripubertal period in Nellore heifers could unveil certain differences in age at puberty because they reach sexual maturity much later than European heifers. The adipose tissue regulates energy metabolism and is an endocrine organ with active participation in reproductive processes .The present study aimed at understanding the functions of the adipose tissue around pubertal time in Nellore heifers. Our strategy was to search for differences in gene expression between prepubertal and pubertal animals. We quantified gene expression in the adipose tissue for Nellore heifers who reached puberty according to either the early or late pattern. This research was done on 30 Nellore heifers monitored weekly from 230 kg bodyweight until the onset of puberty through gynaecological ultrasound examination. The onset of puberty was defined by the presence of corpus luteum in the ovary and blood progesterone > 1 ng/ml. Adipose tissue was collected through subcutaneous biopsy; the first biopsy was done when heifers reached 230 kilos bodyweight and subsequently once a month until they entered puberty. Biopsies were collected of each heifer that reached puberty alongside its half-sister who had not reached puberty. We analysed samples of six early pubertal heifers and their six late pubertal sisters at two different stages: at the time of ovulation and approximately 50 days before ovulation. The RNA was extracted from the biopsies\' tissue and gene expression quantified through RNA sequencing. There were nine genes differentially expressed in pubertal heifers that have been found previously correlated with reproductive traits and/or processes in mammals on other studies. These genes were APOD, CYP17A1, DNMT3B, AKR1C4, TENM1/ODZ3, HPSE, SMPD3, FAM134B and CYP26B1, already found expressed in adipocytes, hypothalamus, ovaries and uterus, corroborating previous knowledge of a link among energy metabolism, reproductive organs and neural influence. By measuring the genetic changes and correlating them with known physiological mechanisms on the nervous system and reproductive organs during puberty, we detected genes expressed here that are related to modifications in the organism as a whole. Therefore the adipose tissue may be regarded as an instrument to indicate what is going on during reproductive processes. The results presented here may aid in a better understanding of genetic changes happening during peripubertal period.